The state of scientific development of the problem of operational and investigative counteraction by criminal police units to the promotion of criminally illegal activities of an organized group or criminal organization - A. V. Filchakov (Bulletin of Kharkiv National University of Internal Affairs)
The article examines the state of scientific development of assistance to criminally illegal activities of an organized group or criminal organization in the context of consideration of various aspects of operational and investigative counteraction to criminal wrongdoing by criminal police units.